Prenatal exposure to valproic acid induces alterations in the expression and activity of purinergic receptors in the embryonic rat brain - Babiec, Lidia; Wilkaniec, Anna; Adamczyk, Agata (Folia Neuropathologica, 2022)
Purinergic signalling is involved in the control of several processes related to brain development, such as neurogenesis and gliogenesis, migration and differentiation of neuronal precursors, synaptogenesis and synaptic elimination to achieve a fully wired and efficient mature brain. Therefore, any deregulation of purine-dependent signalling mediated by stimulation of specific adenosine and purinergic receptor subtypes: P1, P2X, or P2Y, can lead to functional deficits and the development of neuropsychiatric disorders, including autism spectrum disorders (ASD). In this study, we investigated the changes in expression and activity of selected purinergic receptors during rat brain development in an animal model of ASD. Pregnant dams received an intraperitoneal injection of valproic acid (VPA; 450 mg/kg body weight) at embryonic day (ED) 12.5, around the time of neural tube closure. Subsequently, changes in the expression and activity of specific purinergic receptor subtypes were analysed at ED19, an important prenatal stage of brain development. Our results suggest that prenatal VPA exposure leads to a significant increase in the level and activity of adenosinergic receptors A1, A2b and A3, which are involved in the regulation of progenitor cell proliferation and nerve growth, and upregulation of purinergic P2X2/P2X3 receptors, which in turn may contribute to the postnatal neuroanatomical abnormalities and synaptic dysfunction. Conversely, the significant downregulation of P2Y1 and P2X7 receptors, together with their reduced activity in the embryonic VPA brain, may indicate disturbances in the processes of neuronal precursor migration and differentiation, dendritic and axonal formation, and glutamate/GABA imbalance, thereby altering neuronal excitability. In conclusion, defects in purinergic signalling induced by prenatal VPA exposure could have a profound impact on brain development during embryogenesis and on intellectual and behavioural functions after birth. These observations could provide clues for future implementation of potential therapeutic strategies for ASD.